2023
DOI: 10.3390/jcm12041644
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vasovagal Reactions to Needles from Facial Action Units

Abstract: Background: Merely the sight of needles can cause extreme emotional and physical (vasovagal) reactions (VVRs). However, needle fear and VVRs are not easy to measure nor prevent as they are automatic and difficult to self-report. This study aims to investigate whether a blood donors’ unconscious facial microexpressions in the waiting room, prior to actual blood donation, can be used to predict who will experience a VVR later, during the donation. Methods: The presence and intensity of 17 facial action units wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…The importance of the first‐time donor status is well‐established [4, 6, 9, 11, 12]. On the other hand, a few previous studies reported that those who had experienced syncope during a previous donation were at an increased risk of recurrent syncope [15, 16]. As previously reported, our results showed that age was the next most important variable for VVR [4, 6, 11, 12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The importance of the first‐time donor status is well‐established [4, 6, 9, 11, 12]. On the other hand, a few previous studies reported that those who had experienced syncope during a previous donation were at an increased risk of recurrent syncope [15, 16]. As previously reported, our results showed that age was the next most important variable for VVR [4, 6, 11, 12].…”
Section: Discussionsupporting
confidence: 83%
“…A recent systematic review [3] reported risk factors associated with the development of VVR among whole‐blood donors. The following risk factors were associated with an increased risk of syncope: female sex [4–6], lower body weight [7–9], lower estimated blood volume (EBV) [5, 10, 11], young age [4, 6, 11, 12], first‐time donor [4, 6, 9, 11, 12], low resting blood pressure [7], reduced sleep before donation [13, 14], donation location [11] and previous history of symptoms at blood donation [15, 16].…”
Section: Introductionmentioning
confidence: 99%